“English Ramadhan Camp” Meningkatkan Keilmuan Bahasa Inggris Dan Keislaman Di Bulan Ramadhan - Zulfi Zumala Dwi Andriani; Dewi Khawa (IAI Darussalam, 2023)
ABSTRACT: The aim of the program is to design English learning combined with the religious lesson namely Fiqh. The program was conducted in Ramadhan month. The materials of the programs are specialized for public speaking skill improvement such as Speech and Master of ceremony and Fiqh which focuses on sexual health and reproduction for teenagers. The program was implemented in SMK Ibnu Sina Genteng district, Banyuwangi Regency. Through this program, it is hoped to provide opportunities for practice teaching method for IAI Darussalam students assisted by lectures, and to build a tight corporation between IAI Darussalam and community. The result of the program is the students are very enthusiast and having adequate knowledge about public speaking in English as well as a proper knowledge about Fiqh. Keyword: Ramadhan Camp, English Learning, Public Speaking